Dispersión Raman de electrones en puntos cuánticos piramidales (2016)
ABSTRACT: The Raman scattering related with electrons in pyramidal quantum dots is theoretically investigated. The electron Raman differential cross section is calculated making use of analytically determined quantum states within the effective mass approximation. The features of the Raman differential cross section are discussed in terms of their dependence on the changes of the quantum dot geometry.